Coagulopathy in Malnourished Mice Is Sexually Dimorphic and Regulated by Nutrient‐Sensing Nuclear Receptors. Issue 12 (22nd October 2020) - Preidis, Geoffrey A.; Soni, Krishnakant G.; Suh, Ji Ho; Halder, Tripti; Kim, Kang Ho; Choi, Jong Min; Li, Feng; Devaraj, Sridevi; Conner, Margaret E.; Coarfa, Cristian; Jung, Sung Yun; Moore, David D.
Abstract : Liver dysfunction, including coagulopathy, is a prominent feature of protein‐energy malnutrition. To identify mechanisms underlying malnutrition‐associated coagulopathy, we administered a low‐protein low‐fat diet to lactating dams and examined hepatic transcription and plasma coagulation parameters in young adult weanlings. Malnutrition impacted body composition to a greater extent in male versus female mice. Transcriptional profiles suggested opposing effects of nutrient‐sensing nuclear receptors, namely induction of peroxisome proliferator‐activated receptor α (PPARα) targets and repression of farnesoid‐X‐receptor (FXR) targets. Coagulopathy with decreased synthesis of fibrinogen‐α (FGA) and factor 11 (F11) was observed in malnourished male animals but not female animals. In primary mouse hepatocytes, FXR agonist increased and PPARα agonist decreased Fga and F11 messenger RNA expression. Nuclear receptor DNA response elements were identified in the Fga and F11 gene regulatory regions, and opposing effects of FXR and PPARα were confirmed with luciferase assays. Unexpectedly, hepatic PPARα protein was markedly depleted in malnourished male liver and was not enriched on Fga or F11 response elements. Rather, there was loss of FXR binding at these response elements. Reduced PPARα protein was associated with loss of hepatocyte peroxisomes, which are necessary for bile acid biosynthesis, and with decreased concentrations of bile acids that function as FXR ligands, most notably the FXR agonist chenodeoxycholic acid. Conclusion : Malnutrition impairs growth and liver synthetic function more severely in male mice than in female mice. Malnourished male mice are coagulopathic and exhibit decreased hepatocyte peroxisomes, FXR agonist bile acids, FXR binding on Fga and F11 gene regulatory elements, and coagulation factor synthesis. These effects are absent in female mice, which have low baseline levels of PPARα, suggesting that nutrient‐sensing nuclear receptors regulate coagulation factor synthesis in response to host nutritional status in a sex‐specific manner. Abstract : To gain insights into mechanisms underlying coagulopathy in malnutrition, we fed mice a low‐protein, low‐fat diet and assessed hepatic gene expression and plasma coagulation indices. Malnourished males were affected more profoundly than females, and exhibited coagulopathy, decreased expression of fibrinogen‐alpha and factor 11, decreased FXR activation, and decreased FXR binding to regulatory elements on these two coagulation factor genes. These findings are associated with profoundly depleted PPAR‐alpha protein, peroxisome loss, and decreased concentrations of FXR agonist bile acids in malnourished males but not females.